Does Money Matter for U.S. Inflation? : Evidence from Bayesian VARs - Osterholm, Par (IMF Working Papers; Working Paper ;, 2008)
We use Bayesian estimation techniques to investigate whether money growth Granger-causes inflation in the United States. We test for Granger-causality out-of-sample and find, perhaps surprisingly given recent theoretical arguments, that including money growth in simple VAR models of inflation does systematically improve out-of-sample forecasting accuracy. This holds for a long forecasting sample 1960-2005, as well for more recent subperiods, including the Volcker and Greenspan eras. However, the contribution of money to inflation forecasting accuracy is quantitatively limited and tends to be smaller in recent subperiods, in particular in models that also include information on real GDP growth and interest rates.